2021
DOI: 10.1038/s41380-021-01098-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and subcortical brain volumes in bipolar disorders–ENIGMA study in 2735 individuals

Abstract: Individuals with bipolar disorders (BD) frequently suffer from obesity, which is often associated with neurostructural alterations. Yet, the effects of obesity on brain structure in BD are under-researched. We obtained MRI-derived brain subcortical volumes and body mass index (BMI) from 1134 BD and 1601 control individuals from 17 independent research sites within the ENIGMA-BD Working Group. We jointly modeled the effects of BD and BMI on subcortical volumes using mixed-effects modeling and tested for mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 88 publications
(156 reference statements)
6
25
0
Order By: Relevance
“…Aside from the standardization of methods, we also addressed any differences between scanners statistically by using mixed models and including site as a random factor in all analyses. While there are other approaches, this is still by far the most utilized and accepted method for dealing with site effects 27,51 . Information about medications was limited to current usage at the time of scan.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the standardization of methods, we also addressed any differences between scanners statistically by using mixed models and including site as a random factor in all analyses. While there are other approaches, this is still by far the most utilized and accepted method for dealing with site effects 27,51 . Information about medications was limited to current usage at the time of scan.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, previous scientific research has confirmed that subcortical structural abnormalities co-occur with widespread cortical volume reduction even in large-scale studies from the ENIGMA working groups for Sch, BD, and MDD ( 10 12 ). The most consistent findings are enlarged lateral ventricles and reduced hippocampal and amygdala volumes in these disorders.…”
Section: Introductionsmentioning
confidence: 89%
“…McWhinney and colleagues investigated the effects of obesity on subcortical volumes from 1134 individuals with BD and 1601 healthy controls from 13 countries worldwide. 57 They found that 18.4% of the total association between BD and ventricular volume was explained by a higher body mass index (BMI) in BD. Other subcortical regions, including the hippocampus, caudate and thalamus, were robustly associated with BD even after controlling BMI, and there was no interaction between BD and BMI in predicting subcortical brain volumes.…”
Section: Subcortical Structures In Bipolar Disordermentioning
confidence: 99%
“…McWhinney and colleagues investigated the effects of obesity on subcortical volumes from 1134 individuals with BD and 1601 healthy controls from 13 countries worldwide 57 . They found that 18.4% of the total association between BD and ventricular volume was explained by a higher body mass index (BMI) in BD.…”
Section: Subcortical Structuresmentioning
confidence: 99%